David Nabarro: No one will be left behind - David Nabarro (Africa Renewal, 2016)
David Nabarro is the new special adviser to United Nations Secretary-General Ban Ki-moon on sustainable development goals (SDGs), a plan of action for ending poverty adopted by UN member states in September 2015 to replace the Millennium Development Goals. Dr. Nabarro will work with member states to implement SDGs by 2030. The following are excerpts of his interview with Masimba Tafirenyika for Africa Renewal.